2019
DOI: 10.3390/su11154238
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Leachate from Northern Landfill Site in Bloemfontein on Water and Soil Quality: Implications for Water and Food Security

Abstract: Solid waste management in developing cities is a threat to water and food security. The final disposal option for solid wastes is usually landfill sites. Possible contaminants and their impact on surface and groundwater, and soil quality, at the northern solid waste landfill in Bloemfontein city, South Africa, was investigated. Soil samples were analysed for basic cations and heavy metals. A one-point surface leachate, groundwater, and surface water samples were analysed for physicochemical and microbiological… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
28
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(33 citation statements)
references
References 34 publications
(44 reference statements)
3
28
0
2
Order By: Relevance
“…In general, the low heavy metals concentration was indicative of the fact that the southern landfill was primarily a dumping site for municipal, domestic and institutional waste not industrial material (MMM, 2016). Similar findings were observed from the Municipal Bloemfontein Northern solid waste-landfills (Ololade et al., 2019).…”
Section: Resultssupporting
confidence: 85%
See 2 more Smart Citations
“…In general, the low heavy metals concentration was indicative of the fact that the southern landfill was primarily a dumping site for municipal, domestic and institutional waste not industrial material (MMM, 2016). Similar findings were observed from the Municipal Bloemfontein Northern solid waste-landfills (Ololade et al., 2019).…”
Section: Resultssupporting
confidence: 85%
“…The increase in soil pH with depth was therefore not surprising given that it corroborated with the enrichment of basic forming exchangeable cations with a mean range of 24–2573 mgkg- 1 in the order of abundance followed the trend Ca > Mg > K > Na > S > P and Ca > Mg > Na > K > S > P for the respective surface and subsurface horizons. Ololade et al. (2019) observed similar trends for soil profile horizons of sandy clay loam texture with mean pH of 6.6 from the drainage pathways of the Bloemfontein northern landfill.…”
Section: Resultssupporting
confidence: 61%
See 1 more Smart Citation
“…In South Africa Ololade, et al [13] investigated the influence of landfill leachate on the surrounding soil and water quality of the Northern landfill in Bloemfontein and the implication on water and food security. Based on the findings they concluded that most of the parameters analysed were above the permissible limit of SANS241, WHO for drinking water, and DWAF specification for irrigation, an indication that the groundwater was unfit for drinking, domestic, and irrigation purposes.…”
Section: Literature Reviewmentioning
confidence: 99%
“…According to Olalade et al, [7], most dumpsite/landfill are built without engineered liners and leachate collection systems so they function without proper leachate collection and treatment facilities thereby promoting leachate migration with adverse effect on the environment and public health.…”
Section: Introductionmentioning
confidence: 99%